GE_GERICHTE P/16377/2020 vom 17. Dezember 2025 - GE Cour de justice (2025)
ORDONNANCE DE CLASSEMENT;ABUS DE CONFIANCE;USURE(DROIT PÉNAL);ESCROQUERIE;RESTITUTION(EN GENERAL);ORDONNANCE DE SÉQUESTRE | CPP.319; CP.138; CP.157; CP.182; CP.189; CPP.267.al5